Identidade, memória e resistência em A cor da ternura e Ponciá Vicêncio - Silva , Michelle Pinto da (2014)
Introducing itself by means of a language loaded with significance and punctuated by marks of oppression and exclusion, African-Brazilian literature, by conveying the word, ensures the black community breaking a silence for a long time by the subjugation and subservience proportioned by enslavement. Such texts increasingly affirm themselves in the scenery of the Brazilian literary canon, when they turn to the way of the fights that impel the black population to seek for their personal affirmation and for the guarantee of their rights as citizens. Under this angle we´ll analyze here the works A cor da ternura (1998), by Geni Guimarães and Ponciá Vicêncio (2003), by Conceição Evaristo, in a comparative study of the protagonist´s discourses in what concerns the issues of identity, presented through a plot of memoirs in which the life experiences exposed by them suggest actions of combat against and resistance to racial prejudice and oppression on the part of the dominant society. In this work we use as theoretical basis the studies made by Anna Freud (1976); Halbwachs (1990); Bergson (1999); Landowski (2002); Giddens (2002); Bauman (2005); Seligmann-Silva (2005); Hall (2006/2013); Fanon (2008); (2010); Castells (2010) and Candau (2012), among others.